Development of A MATLAB Application for Evaluating the Performance of Photovoltaic System - Zamzuri Ariffin, Ammar Sofi; Mohamad Nor, Ahmad Fateh (Evolution in Electrical and Electronic Engineering, 2023)
This research focuses on the development of a MATLAB application for evaluating the performance of a photovoltaic system by using a Graphical user Interface (GUI) platform. PV systems need to be evaluated because to performance of photovoltaic system output depends on Sunray which will eventually be affected in its performance evaluation because of the inconsistency of photovoltaic panel input values. Output power is dramatically reduced when photovoltaic (PV) modules are subjected to varying solar irradiation which certain areas are partially shaded. This research explained how the performance of a photovoltaic system may be examined using three distinct methods: acceptance ratio, energy performance index, and final system yield. Estimating the performance of a solar system using a computer approach, has been made. Acceptance Ratio, Energy Performance Index, measured Final System Yield, and predicted Final System Field were 0.134, 63.769%, 131.579 , and 206.338 respectively. While, the computational result was compared to the GUI application, it shows that differences of data are very small yet it makes the application function as expected Result shows performance of the photovoltaic system was worse than expected due to many aspects such as surrounding and system efficiency. GUI applications can be used and are eco-friendly without having users to go through complicated processes to install the application. Objectives that were introduced have been achieved throughout this research.